Introduction to holography - Toal, Vincent (Series in Optics and Optoelectronics, 2022)
This fully updated second edition of Introduction to Holography provides a theoretical background in optics and holography with a comprehensive survey of practical applications. It is intended for the non-specialist with an interest in using holographic methods in research and engineering. The text assumes some knowledge of electromagnetism, although this is not essential for an understanding of optics, which is covered in the first two chapters. A descriptive approach to the history and principles of holography is followed by a chapter on volume holography. Essential practical requirements for successful holographic recording are explained in detail. Recording materials are considered with detailed discussions of those in common use. Properties peculiar to holographically reconstructed images are emphasised as well as applications for which holography is particularly suitable. Mathematical tools are introduced as and when required throughout the text with important results derived in detail. In this new edition, topics such as photopolymers, dynamic holographic displays, holographic optical elements, sensors, and digital holography are covered in greater depth. New topics have been added, including UV and infrared holography, holographic authentication and encryption, as well as particle beam, X-ray, and acoustic holography. Numerical problems are provided at the end of each chapter. This book is suitable for undergraduate courses and will be an important resource for those teaching optics and holography. It provides scientists and engineers with knowledge of a wide range of holographic applications in research and industry, as well as an understanding of holography's potential for future use.